Adivasi art and activism: Curation in a nationalist age - Tilche, Alice (New Delhi Orient blackswan private Limited, 2022)
As India consolidates an aggressive model of economic development, indigenous tribal people known as adivasis continue to be overrepresented among the country's poor. Adivasis make up more than eight hundred communities in India, with a total population of more than 100 million people who speak more than three hundred different languages. Although their historical presence is acknowledged by the state and they are lauded as a part of India's ethnic identity today, their poverty has been compounded by the suppression of their cultural heritage and lifestyle.
Keywords: Social problems in art exhibitions; Interdisciplinary approach to knowledge; India social conditions